THE UTILIZATION BEHAVIOUR OF DENTAL HEALTH SERVICES AMONG PREGNANT WOMEN IN SEMARANG CITY - Nafisah - -; Sri Achadi Nugraheni; Farid Agushybana (Dian Nuswantoro Semarang, 2020)
Background: Pregnancy had an impact on oral health that cause pregnant women susceptible to dental caries and periodontal disease. Poor oral health conditions of pregnant women could had an impact on the mother herself and also the fetus.Objective: The purpose of this study was to determine the utilization of oral health services among pregnant women in Semarang city, and the factors that associated with it. Method: This study was an analytic observational with case controlled design using a questionnaire involving 96 pregnant women. The questions including respondent characteristics, knowledge, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action and self-efficacy regarding the used of oral health services. Results: The results showed that more than half of respondents (54.2%) already used oral health services during pregnancy. The variables which together had an effect on the utilization of oral health services are knowledge (p value=0.000, OR=17.343) perceived severity (p value=0.001, OR=10.416) and cues to action (p value=0.007, OR=7.403). Conclusion: This studied concluded that the knowledge, perceived severity and cues to action affect significantly affect to utilization of oral health services among pregnant women.Keywords: Pregnant women, dental health, utilization